Protection and Reconstruction of Schooling in Conflict Zones Reflections from the Field - Ilyas, Mohammad (JOURNAL OF INDIAN EDUCATION, 2023)
The paper outlines the remedial measures, protective and reconstructive steps to protect schooling in conflict zones that are based on the information collected through the questionnaires, interviews and focus group discussion with the respondents (n=105) in Jammu and Kashmir. The union territory of Jammu and Kashmir has been hit by unrest for nearly three decades, and this situation of unrest prevailing in the region has impacted the education sector miserably. The present study is based on a descriptive survey method, intended to understand the broad trends of experiences, and factors influencing the experiences of various stakeholders. The paper is mostly based on the respondents’ perceptions of the actions that must be performed to maintain the operation of schools as well as to improve the education system, which appears to be mistreated by conditions and problems in the way of protecting education. The type of protective measures discussed here are physical protection, community involvement, psychological protection and the role of government and NGOs that attempts to lessen the effect of armed conflict on schooling. Ensuring access to education need to be the priority and primary concern of the authorities as well as different stakeholders in education of the conflict hit zones.